2001
DOI: 10.1051/0004-6361:20000426
|View full text |Cite
|
Sign up to set email alerts
|

Optical surface photometry of a sample of disk galaxies

Abstract: This work presents the structural decomposition of a sample of 11 disk galaxies, which span a range of different morphological types. The U , B, V , R, and I photometric information given in Paper I (color and color-index images and luminosity, ellipticity, and position-angle profiles) has been used to decide what types of components form the galaxies before carrying out the decomposition. We find and model such components as bulges, disks, bars, lenses and rings.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
114
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 83 publications
(120 citation statements)
references
References 33 publications
6
114
0
Order By: Relevance
“…This can be achieved by performing a photometric decomposition of the galaxy surfacebrightness distribution. The galaxy light is usually modeled as the sum of the contributions of the different galactic components, i.e., bulge and disk, and eventually lenses, bars, spiral arms, and rings (Prieto et al 2001;Aguerri et al 2005). A number of two-dimensional parametric decomposition techniques have been developed to achieve this aim (e.g., Simard 1998;Khosroshahi et al 2000;Peng et al 2002;de Souza et al 2004;Laurikainen et al 2005;Pignatelli et al 2006;Méndez-Abreu et al 2008).…”
Section: Intrinsic Shape Of Disk Galaxiesmentioning
confidence: 99%
“…This can be achieved by performing a photometric decomposition of the galaxy surfacebrightness distribution. The galaxy light is usually modeled as the sum of the contributions of the different galactic components, i.e., bulge and disk, and eventually lenses, bars, spiral arms, and rings (Prieto et al 2001;Aguerri et al 2005). A number of two-dimensional parametric decomposition techniques have been developed to achieve this aim (e.g., Simard 1998;Khosroshahi et al 2000;Peng et al 2002;de Souza et al 2004;Laurikainen et al 2005;Pignatelli et al 2006;Méndez-Abreu et al 2008).…”
Section: Intrinsic Shape Of Disk Galaxiesmentioning
confidence: 99%
“…Secondly, for systems with small bulges MacArthur et al (2003) showed that results from one-dimensional photometry are equivalent to those derived from two-dimensional fits (as required by this work). The resulting sample is comprised of 61 galaxies taken from Möllenhoff (2004), MacArthur et al (2003), Prieto et al (2001) and Pompei & Natali (1997). Since MacArthur et al had measurements in B V R H, their R band scalelengths were converted to I band scalelengths by multiplying them by a factor of 0.981.…”
Section: Application To Local Universe Disk Galaxiesmentioning
confidence: 99%
“…In this context, the bulge is photometrically defined as the extra component dominating the galaxy light above the surfaceluca.costantin@studenti.unipd.it brightness profile of the disk extrapolated in the inner regions of the galaxy. The bulge surface brightness is usually fitted with a Sérsic law spanning a large range of profile shapes, whereas the disk surface brightness is usually fitted with an exponential law (Andredakis 1998;Prieto et al 2001;Aguerri et al 2005;Méndez-Abreu et al 2017). …”
Section: Introductionmentioning
confidence: 99%